International portfolio diversification, skewness and the role of gold - LUCEY, BRIAN MICHAEL (ESC Lille, 2007)
The paper examines the optimal allocation of assets in well diversified equity based portfolio where the investor is concerned not only with mean and variance but also with the skewness of the returns.
PUBLISHED
Keywords: Economics; Gold